Detection of Bovine TMEM95 p.Cys161X Mutation in 13 Chinese Indigenous Cattle Breeds - Sihuan Zhang; Kun Peng; Guoliang Zhang; Yang Cao; Meng Zhang; Hong Chen; Chuzhao Lei; Xianyong Lan; Yumin Zhao (Animals, 2019)
Chinese indigenous cattle breeds have abundant genetic resources, which are valuable for the molecular breeding of cattle around the world. Thus, identifying important candidate genes and their genetic markers is very important for cattle molecular breeding. A previous study found that a nonsense mutation (rs378652941, c.483C > A, p.Cys161X) in the bovine transmembrane protein 95 gene (TMEM95) seriously reduced the reproductive performance in bulls, but few studies have detected this mutation in Chinese indigenous cattle breeds. Since the mutation c.483C > A may serve as a potential genetic marker for selecting higher fertility bulls, in the present study, using tetra-primer amplification refractory mutation system PCR (T-ARMS-PCR), forced PCR restriction fragment length polymorphism (forced PCR-RFLP), and DNA sequencing methods, the mutation c.483C > A was detected in 765 individuals from 13 Chinese cattle breeds. However, the results showed that this mutation did not exist at this locus in our analyzed breeds. Interestingly, we identified a newly frameshift insertion/deletion (indel) mutation (NC_037346.1: g.27056998_27057000delCT) in the bovine TMEM95 gene in 11 cattle breeds, which changed the location of the termination codon and changed the 16 amino acids in the C-terminal to 21 amino acids. Combined with previous studies, our study provides evidence that in Chinese cattle breeds the mutation c.483C > A cannot be used as a genetic marker in molecular breeding.